2006
DOI: 10.1080/08905430500522030
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability Among Isolates ofPlesiomonas shigelloidesfrom Fish, Human Clinical Sources and Fresh Water, Determined by RAPD Typing

Abstract: Plesiomonas shigelloides has been a suspected pathogen for the past 40 years. Random amplified polymorphic DNA (RAPD) analysis with two random primers was used to examine the genetic diversity among 26 strains of P. shigelloides: 10 from fresh water, 6 from fish, and 10 from human clinical sources. There was notable genetic variability among most of the isolates, and none of the isolates had the same composite RAPD profile. Our results indicate that most of the isolates from the same source grouped together an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…The dendrogram did not reveal geographical relations among strains since isolates from spatially unrelated samples were grouped in the same cluster. The results of our RAPD analysis are in accordance with the findings of Gu et al [63] who used the RAPD technique to determine genetic variability among 26 isolates from fresh water (10 isolates), fish (6 isolates) and human clinical isolates (10 isolates) and found a high genetic variability among most of the isolates while none of the isolates had the same composite RAPD profile. Similarly, among 24 strains belonging to nine O:H serovars isolated from humans, animals and the environment, 22 different RAPD-PCR patterns were found [64].…”
Section: Discussionsupporting
confidence: 91%
“…The dendrogram did not reveal geographical relations among strains since isolates from spatially unrelated samples were grouped in the same cluster. The results of our RAPD analysis are in accordance with the findings of Gu et al [63] who used the RAPD technique to determine genetic variability among 26 isolates from fresh water (10 isolates), fish (6 isolates) and human clinical isolates (10 isolates) and found a high genetic variability among most of the isolates while none of the isolates had the same composite RAPD profile. Similarly, among 24 strains belonging to nine O:H serovars isolated from humans, animals and the environment, 22 different RAPD-PCR patterns were found [64].…”
Section: Discussionsupporting
confidence: 91%
“…The data obtained ensure that strains within the same serovar can generally be differentiated at a genomic level. RAPD has also been used for genotyping P. shigelloides isolates from fish, human clinical sources, and fresh water (Gu et al 2006). Final conclusions were the same as in the above work: P. shigelloides shows a significant level of genetic variability among the isolates.…”
Section: Discussionmentioning
confidence: 65%
“… Plesiomonas shigelloides , represented as a single species in the genus Plesiomonas , is a Gram-negative, flagellated, facultative anaerobic, rod-shaped bacterium. It is widespread in aquatic environments and is also found in a wide range of hosts, including humans, dogs, fish, sheep, cows, pigs, and turkey vultures ( 2 ). A serotyping scheme using antigenic variation in the lipopolysaccharide (O-antigen) and flagella (H-antigen) has been used for classification, identification, and epidemiological investigation of P. shigelloides .…”
Section: Introductionmentioning
confidence: 99%
“…Presently, phylogenetic analysis based on 5S and 16S data and on data from multilocus sequence typing (MLST) indicated that this taxon is rooted within Enterobacteriaceae , but not within the Proteus clade ( 6 9 ). The genetic diversity of this bacterium has been verified by pulsed-field gel electrophoresis (PFGE), random amplified polymorphic DNA (RAPD) typing, and MLST ( 2 , 9 , 10 ). However, researchers who used the previously available methods encountered difficulty in obtaining high-resolution taxonomy as well as detailed information on the genetic diversity and phylogenetic relationships of P. shigelloides .…”
Section: Introductionmentioning
confidence: 99%